Production of haploid plants from ten hybrids of bread wheat (Tritcum aestivum L.) through wide hybridization with maize (Zea mays L.) - Torres, L.E.=700 1 Bima, P.; Maich, R.; Badiali, O.J.J.
(Es, En)
Ilus., 27 ref.
Keywords: TRITICUM AESTIVUM; HAPLOIDIA; HIBRIDACION INTERESPECIFICA; ZEA MAYS; ARGENTINA; AGRISCENTIA